1992
DOI: 10.1152/ajpregu.1992.263.4.r775
|View full text |Cite
|
Sign up to set email alerts
|

Stress in birds due to routine handling and a technique to avoid it

Abstract: The stress that might result in animals from the routine handling that most experimental studies involve, e.g., weighing, injecting, and blood sampling, is usually assumed to be minimal when the animals look quiet. However, the intensity of this stress remains largely ignored. We have developed a system that allows blood samples to be taken from freely behaving geese without entering the animal room. In these entirely undisturbed geese, the humoral indexes of stress, i.e., blood levels of catecholamines, corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 0 publications
2
49
1
Order By: Relevance
“…Typically, studies of this type require that the experimental subjects be restrained (Bech et al, 1972;Keijer and Butler, 1982) or at least in captivity (Lasiewski, 1972). Given the stress experienced by these experimental subjects (Le Maho et al, 1992) and the attendant physiological complications (Axelrod and Reisine, 1984), care must be exercised in interpreting the results. Recently, and to our knowledge for the first time, Le Boeuf et al (2000) equipped free-living elephant seals Mirounga angustirorostris with a system for recording rates of respiration during normal diving and travelling behaviour (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, studies of this type require that the experimental subjects be restrained (Bech et al, 1972;Keijer and Butler, 1982) or at least in captivity (Lasiewski, 1972). Given the stress experienced by these experimental subjects (Le Maho et al, 1992) and the attendant physiological complications (Axelrod and Reisine, 1984), care must be exercised in interpreting the results. Recently, and to our knowledge for the first time, Le Boeuf et al (2000) equipped free-living elephant seals Mirounga angustirorostris with a system for recording rates of respiration during normal diving and travelling behaviour (cf.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which tethering reshapes 'normal' behavior in these paradigms is likely substantial. Though, perhaps less stressful than direct handling of the animal [21], tethering results in abnormal responses including decreased exploratory activity, increased stereotypies, aggression and immobility, as well as an altered stress hormone response [22][23][24][25][26]. Furthermore, tethering is practical only in the study of behaviors of animals in isolation and is limited to a subset of behaviors, which present a low risk of entanglement of the animal with its cable.…”
Section: Studies In Tethered Animalsmentioning
confidence: 99%
“…This is the case, not only because the physical act of injection may itself terminate the behavior, but also because it is well known that stress associated with an injection may substantially modify a subject's behavior. In animals, even minor routine handling procedures can induce a marked stress, although the animal has been trained to this procedure and looks quiet [21]. Furthermore, it has been suggested that the mode of administration of a drug-either by manual injection or selfadministration-may result in different effects on brain metabolism [59].…”
Section: Mode Of Administration Of the Radiotracermentioning
confidence: 99%
“…Handling and bleeding may trigger the glucocorticoid levels to rise, which is commonly used as an indication of short-term stress (e.g. Wingfield et al 1992;LeMaho et al 1992;Cockrem and Silverin 2002;Müller et al 2006). In fact, standardised handling protocols have been widely used to assess the hypothalamic-pituitary-adrenal axis response.…”
Section: Introductionmentioning
confidence: 99%